The Application of Spleen-Preserving Splenic Regional Laparoscopic Lymphadenectomy with Spleen Kept In Situ and Laparotomy with Spleen Lifted Out of the Abdomen for Locally Advanced Proximal Gastric Cancer: A Retrospective Study - Changrong Que; Shuangming Lin; Yibin Zhu; Dongbo Xu (Gastroenterology Research and Practice)
Background and Purpose. Findings whether laparoscopic lymphadenectomy with spleen kept in situ or laparotomy with spleen lifted out of the abdomen is more effective remain inconclusive. This study is aimed at comparing outcomes of spleen-preserving splenic regional laparoscopic lymphadenectomy with spleen kept in situ versus laparotomy with spleen lifted out of the abdomen for locally advanced proximal gastric cancer. Methods. Data from patients with locally advanced proximal gastric cancer were collected from January 2011 to January 2014. A total of 246 patients were identified who received D2 radical total gastrectomy together with spleen-preserving splenic regional lymphadenectomy. Of those patients, 87 patients underwent laparoscopic splenic regional lymphadenectomy with spleen kept in situ (LSKS-SRLA) and 159 patients underwent laparotomy with spleen lifted out of the abdomen (LSLA-SRLA). Surgical outcomes and long-term outcomes were compared between the two groups. Results. The total number of lymph node dissection, intraoperative blood loss volume, intraoperative injury cases, and postoperative complications had no statistically significant difference between the two groups. The number of splenic regional lymph node dissections was 3.90±1.05 per case in the LSLA-SRLA group and 2.89±1.04 in the LSKS-SRLA group. The operation time, length of the incision, and hospital days were shorter in the LSKS-SRLA group. The total recurrence and metastatic rates and 3-year cumulative survival rate had no statistically significant difference between the two groups. Conclusions. Similar long-term outcomes were achieved in the LSKS-SRLA and LSLA-SRLA groups for locally advanced proximal gastric cancer. However, in the aspects of surgical time, length of incision, and postoperative recovery, the LSKS-SRLA group had obvious advantages.